Apatinib Inhibits Cell Proliferation and Induces Autophagy in Human Papillary Thyroid Carcinoma via the PI3K/Akt/mTOR Signaling Pathway - Meng, Xiangrui; Wang, Huijuan; Zhao, Jingzhu; Hu, Linfei; Zhi, Jingtai; Wei, Songfeng; Ruan, Xianhui; Hou, Xiukun; Li, Dapeng; Zhang, Jun; Yang, Weiwei; Qian, Biyun; et al. (Frontiers in Oncology, 2020)
Background: Patients with metastatic radioiodine-refractory papillary thyroid carcinoma (PTC) have limited options for treatment and a poor prognosis. There is an urgent need to develop new drugs for clinical application. Apatinib is a novel small molecule tyrosine kinase inhibitor that is highly selective for vascular endothelial growth factor receptor-2 (VEGFR2) and exhibits antitumor effects in a variety of solid tumors. It has shown safety and efficacy in radioiodine-refractory differentiated thyroid cancer, but the mechanism underlying the antitumor effect is unclear. In this report, we explored the effects of apatinib on PTC in vitro and in vivo. Methods: VEGFR2 expression level was evaluated by IHC, qPCR and WB. The effect of apatinib was assessed in terms of cell viability, colony formation and transwell assay in vitro, and tumor growth rate in vivo. Protein levels of signaling pathway were determined by western blot. Autophagy level was assessed by western blot, IF and transmission electron microscopy. Results: We found that high VEGFR2 expression is associated with tumor size, T stage and lymph node metastasis in patients with PTC and that apatinib inhibits PTC cell growth, promotes apoptosis, and induces cell cycle arrest through the PI3K/Akt/mTOR signaling pathway. Moreover, apatinib induces autophagy, and pharmacological inhibition of autophagy or small interfering RNA targeting autophagy-associated gene 5 (ATG5) can further increase PTC cell apoptosis. Conclusion: Our data suggest that apatinib can induce apoptosis and autophagy via the PI3K/Akt/mTOR signaling pathway in the treatment of PTC, and autophagy is a potential novel target for future therapy in resistant PTC.